2005
DOI: 10.1103/physreve.72.016701
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regimes of fluids simulated by multiparticle-collision dynamics

Abstract: We investigate the hydrodynamic properties of a fluid simulated with a mesoscopic solvent model. Two distinct regimes are identified, the "particle regime" in which the dynamics is gas-like, and the "collective regime" where the dynamics is fluid-like. This behavior can be characterized by the Schmidt number, which measures the ratio between viscous and diffusive transport. Analytical expressions for the tracer diffusion coefficient, which have been derived on the basis of a molecularchaos assumption, are foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
236
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(253 citation statements)
references
References 42 publications
16
236
0
Order By: Relevance
“…Over the last decades various mesoscopic simulation methods have been developed to bridge such an enormous gap. Here, we employ an especially convenient hybrid scheme that describes the solvent by MPC which is a coarse-grained particle-based method [23][24][25][26][27][28], while the interactions of the Janus particle with the solvent are simulated by standard molecular dynamics (MD).…”
Section: Simulation Of a Janus Microswimmer In Solutionmentioning
confidence: 99%
“…Over the last decades various mesoscopic simulation methods have been developed to bridge such an enormous gap. Here, we employ an especially convenient hybrid scheme that describes the solvent by MPC which is a coarse-grained particle-based method [23][24][25][26][27][28], while the interactions of the Janus particle with the solvent are simulated by standard molecular dynamics (MD).…”
Section: Simulation Of a Janus Microswimmer In Solutionmentioning
confidence: 99%
“…The affect is particularly pronounced, however, for the self-diffusion coefficient, for which there is no collisional contribution. Indeed, Ripoll et al [25,26] have observed that the self diffusion coefficient is significantly larger than the theoretical prediction of Ref. [17,20] for small λ/a.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that p 2 is related to the quantity ζ 1 of Ref. [26], which denotes the number of particles that are neighbors of a given particle for two consecutive time steps; more precisely, p 2 = (ζ 1 − 1)/(M − 1). Figure 14 is a plot of simulation results for δH(2τ ) as a function of λ/a for three different values of the collision angle α.…”
Section: B Self-diffusion Coefficientmentioning
confidence: 99%
“…The fiber or chain segments will be coupled to this hydrodynamic solvent by also taking part in the rotation procedure. With appropriately chosen simulation parameters, 48 such an approach leads to correct hydrodynamic behavior of polymeric chains, as shown recently by Winkler et al 17 From the point of view of the latter work, this paper is an extension of the hydrodynamic method to also include uncrossability of the chains. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 91%
“…Important developments in this area are lattice Boltzmann ͑when extensions to allow for thermal fluctuations are included͒, 34-37 dissipative particle dynamics, 38,39 and multiparticle collision dynamics ͑MPCD͒. 17,[40][41][42][43][44][45][46][47][48][49][50][51][52] The latter, in its original implementation, 40 is also known as stochastic rotation dynamics ͑SRD͒. All these mesoscopic simulation techniques account for correlated motion of the solvent which leads to long-range HIs.…”
Section: Introductionmentioning
confidence: 99%